2010
DOI: 10.1242/jeb.036871
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between aquaporin and water permeability in response to vasotocin, hydrin and β-adrenergic effectors in the ventral pelvic skin of the tree frogHyla japonica

Abstract: SUMMARYThe ventral pelvic skin of the tree frog Hyla japonica expresses two kinds of arginine vasotocin (AVT)-stimulated aquaporins (AQP-h2 and AQP-h3), which affect the capacity of the frog's skin to absorb water. As such, it can be used as a model system for analyzing the molecular mechanisms of water permeability. We investigated AQP dynamics and water permeability in the pelvic skin of H. japonica following challenge with AVT, hydrins (intermediate peptides of pro-AVT) and -adrenergic effectors. In the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…The Bayesian analyes show that the wholly aquatic Western-clawed frog has two paralogs of AQP5 , a canonical form ( AQP5 , formerly annotated as AQP-x5 , [28]) and a related paralog ( AQP5L , formerly annotated as AQP2 ) encoded between two AQP6 genes, the urinary bladder-type ( AQP6ub ) and the ventral skin type ( AQP6vs ) formerly identified as (h2-like and h3-like) type-a2 anuran specific aquaporins [23], [24], [32]. Amongst other Anura the Bayesian data provide statistical support for three paralogs of AQP6 (see Table S2), the urinary bladder type ( AQP6ub ) and two paralogs ( AQP6vs1 , -6vs2 ) that mediate cutaneous hydration through the ventral skin of semi-aquatic and semi-terrestrial anurans [33], [35]. Canonical AQP2 (formerly annotated as AQP-h2k or HC-2, [25], [26]) is found in the genomes of Anura, including the arboreal Pacific treefrog ( Pseudacris regilla ) and the aquatic green frog ( Rana clamitans ), but the absence of an assembled linkage map currently precludes comparison of the loci.…”
Section: Resultsmentioning
confidence: 85%
“…The Bayesian analyes show that the wholly aquatic Western-clawed frog has two paralogs of AQP5 , a canonical form ( AQP5 , formerly annotated as AQP-x5 , [28]) and a related paralog ( AQP5L , formerly annotated as AQP2 ) encoded between two AQP6 genes, the urinary bladder-type ( AQP6ub ) and the ventral skin type ( AQP6vs ) formerly identified as (h2-like and h3-like) type-a2 anuran specific aquaporins [23], [24], [32]. Amongst other Anura the Bayesian data provide statistical support for three paralogs of AQP6 (see Table S2), the urinary bladder type ( AQP6ub ) and two paralogs ( AQP6vs1 , -6vs2 ) that mediate cutaneous hydration through the ventral skin of semi-aquatic and semi-terrestrial anurans [33], [35]. Canonical AQP2 (formerly annotated as AQP-h2k or HC-2, [25], [26]) is found in the genomes of Anura, including the arboreal Pacific treefrog ( Pseudacris regilla ) and the aquatic green frog ( Rana clamitans ), but the absence of an assembled linkage map currently precludes comparison of the loci.…”
Section: Resultsmentioning
confidence: 85%
“…Like AVT, hydrins stimulate osmotic water movement across the skin and bladder but are devoid of antidiuretic activity in the kidney (19,24). Hydrins are only present in anuran amphibians, and we found that hydrin 1 and hydrin 2, as well as AVT, have stimulatory effects on the water permeability across the pelvic skin in H. japonica (21). The third objective of this study was to extend these observations and compare them with the response of the Ranid and Bufonid species to AVT.…”
mentioning
confidence: 60%
“…Water permeability was measured across isolated skin from the pectoral, pelvic, and hindlimb regions of B. marinus and the Rana species. Animals were immersed in water for 30 min before being killed to ensure a fully hydrated state for control observations (21). The isolated skin was washed with Ringer solution and then mounted between two chambers connected by an opening having a diameter of 1 cm.…”
Section: Methodsmentioning
confidence: 99%
“…Each skin was given 2 30-minute washes with Ringer solution, and then its water permeability was measured basically as reported previously (19,25). Using a modified Ussing chamber, water movement was recorded over a 45-minute period after a 30-minute preincubation with Ringer solution alone, as the control, or with 10 Ϫ8 M AVT in the serosal chamber.…”
Section: Experimental Protocol For Water Permeability In Vitromentioning
confidence: 99%